Media Coverage, Corporate Social Responsibility and Earnings Management: China Evidence - Zeng, Wanqing (2022)
This study aims to evaluate the influence of CSR and media coverage on earnings management, as well as the moderating effect of media coverage. This study uses multiple regression models to analyse these relationship for 1048 Chinese listed companies from 2010 to 2017. The results indicate that CSR reduces accrual-based earnings management but has no effect on real earnings management. However, the responsibility of corporations to prioritise shareholder interests hinders real earnings management. Moreover, media coverage raises accruals while decreasing real earnings management. I also discovered that media coverage has no moderating effect. In addition, this study conducts additional tests of the three components of real earnings management and concludes that CSR would interfere with modifying production costs and media coverage would decrease abnormal CFO and discretionary expenditures while increasing production costs. This study concludes with a robustness test by varying media coverage factors and an alternative analysis model on moderating influence, which validate the results.